Regional Tissue Oxygen Extraction and Severity of Anemia in Very Low Birth Weight Neonates: A Pilot NIRS Analysis - Mintzer, Jonathan P.; Parvez, Boriana; La Gamma, Edmund F. (American Journal of Perinatology, 2018)
Objective Anemia causes blood flow redistribution and altered tissue metabolic behavior to sustain homeostatic oxygen consumption. We hypothesized that anemia severity would correlate with increased regional fractional tissue oxygen extraction among premature neonates.Study Design Regional oxygen extraction was calculated using pulse oximetry and near-infrared spectroscopy data among neonates <1,250 g during their first 10 postnatal days. Oxygen extraction was assessed for correlations with raw hematocrit levels and following grouping into hematocrit quartiles.Results Twenty-seven neonates with gestational age 27 ± 2 weeks and birth weight 966 ± 181 g underwent 116 hematocrit determinations. Cerebral and flank oxygen extraction inversely correlated with hematocrit (cerebral r = −0.527, p = 0.005; flank r = −0.485, p = 0.01). Increased cerebral oxygen extraction was observed for the lowest three hematocrit quartiles (Q1 0.26 ± 0.08, p = 0.004; Q2 0.24 ± 0.09, p = 0.01; Q3 0.25 ± 0.09, p = 0.03; all compared with Q4 0.18 ± 0.10). Increased flank oxygen extraction occurred for the lowest two quartiles (Q1 0.36 ± 0.12, p < 0.001; Q2 0.35 ± 0.11, p < 0.001; compared with Q4 0.22 ± 0.13). Splanchnic oxygen extraction demonstrated no similar correlations.Conclusion Increases in tissue oxygen extraction may indicate early pathophysiologic responses to nascent anemia in premature neonates.
Keywords: anemia; hematocrit; neonate; near-infrared spectroscopy; oxygen extraction; regional oxygenation